2018
DOI: 10.1186/s40792-018-0494-4
|View full text |Cite
|
Sign up to set email alerts
|

Successful conversion surgery for unresectable gastric cancer with giant para-aortic lymph node metastasis after downsizing chemotherapy with S-1 and oxaliplatin: a case report

Abstract: BackgroundAlthough patients with stage IV gastric cancer who respond well to systemic chemotherapy can be treated with gastrectomy, the prognosis of patients with unresectable gastric cancer with para-aortic lymph node metastasis is poor. We herein report a case of remnant gastric cancer with para-aortic lymph node metastasis that was treated with potentially curative conversion surgery after showing a complete response to chemotherapy with S-1 and oxaliplatin (SOX).Case presentationAn 81-year-old man was diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Many investigators have demonstrated the prognostic impact of conversion surgery after chemotherapy for stage IV gastric cancer [ 6 8 ]. However, in most reports, conversion surgery was performed in responders after first-line chemotherapy [ 9 11 ], and there are few reports of conversion surgery in responders after second-line chemotherapy with RAM and PTX. Herein, we report a case of long-term survival of a patient with gastric cancer and liver metastases who underwent conversion surgery due to partial response to systemic second-line treatment with RAM plus PTX.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have demonstrated the prognostic impact of conversion surgery after chemotherapy for stage IV gastric cancer [ 6 8 ]. However, in most reports, conversion surgery was performed in responders after first-line chemotherapy [ 9 11 ], and there are few reports of conversion surgery in responders after second-line chemotherapy with RAM and PTX. Herein, we report a case of long-term survival of a patient with gastric cancer and liver metastases who underwent conversion surgery due to partial response to systemic second-line treatment with RAM plus PTX.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a few case reports on conversion surgery for gastric cancer [5][6][7], none describe a case that was initially diagnosed as cancer of unknown primary (CUP). Here we report a case of successful conversion surgery that was performed after a cervical lymphadenectomy and a bilateral oophorectomy, wherein definitive diagnosis of gastric cancer could only be established about 2 years after an initial diagnosis of CUP.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that when patients present with para-aortic lymph node metastasis, dissection of para-aortic lymph nodes has survival benefits [11,12]. In the past, para-aortic lymph node metastasis is defined as distal metastasis (M1) in TNM staging, in Japan, when carrying out D2 radical surgery and N1 and N2 lymph node dissection, routine dissection of para-aortic lymph nodes is also performed [13,14]. Furthermore, in some medical centers, para-aortic lymph node dissection is also used as a routine surgical procedure to improve the prognosis of advanced gastric cancer [15,16].…”
Section: Introductionmentioning
confidence: 99%